Spillovers of the United States' unconventional monetary policy to emerging Asia: The bank lending channel - Ying Xu; Hai Anh La (Asian Development Bank Institute (ADBI), 2016)
This paper assesses the spillover effects of the United States' unconventional monetary policy (i.e., quantitative easing programs adopted during 2008-2014) on the Asian credit market. With a focus on cross-border bank lending, we employed firm-level loan data with regard to the syndicated loan market and measured the international bank lending channel through changes in United States dollar-denominated loans extended to Asian borrowers. We found that the growth of dollar credit in Asia increased substantially in response to quantitative easing in the United States financial market. The results of this study confirm the existence of the bank lending channel in Asia and emphasize the role of credit flows in transmitting financial conditions. The paper also provides new evidence of cross-border liquidity spillover in the syndicated loan market. We found that the overall spillover effect was large but differed significantly in Asia by types of borrowing firms, financing purposes, and loan terms at different stages of the quantitative easing programs. The paper concludes with a discussion of relevant policy implications for the region.
Keywords: F21; F36; G01; G21; G28; 330; Spillovers; unconventional monetary policy; UMP; United States; Asian credit market; credit flows; spillover effects; cross-border liquidity; bank lending channel